2008
DOI: 10.2215/cjn.04421007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Best Practices in Dialysis Care

Abstract: Background and objectives: Because there is wide variation in case-mix adjusted outcomes across dialysis facilities, it is possible that top-performing facilities use practices not shared by others. We sought to catalogue "best practices" that may account for interfacility variations in outcomes.Design, setting, participants, & measurements: This multidisciplinary study identified candidate best practices in dialysis through a staged process, including systematic review, cognitive interviews, and a national "v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
(29 reference statements)
1
33
0
Order By: Relevance
“…There was however a substantial increase in morale when the TNC model was adopted confirming the findings of numerous studies that work group teamwork leads to higher staff job satisfaction, increased patient safety, improved quality of care, and greater patient satisfaction [11,12] . Another study reported that participants' levels of job satisfaction with current position and satisfaction with occupation were both higher when they rated their teamwork higher [13] and these findings suggest that efforts to improve teamwork and ensure adequate staffing in acute settings can improve staff satisfaction.…”
Section: Discussionsupporting
confidence: 72%
“…There was however a substantial increase in morale when the TNC model was adopted confirming the findings of numerous studies that work group teamwork leads to higher staff job satisfaction, increased patient safety, improved quality of care, and greater patient satisfaction [11,12] . Another study reported that participants' levels of job satisfaction with current position and satisfaction with occupation were both higher when they rated their teamwork higher [13] and these findings suggest that efforts to improve teamwork and ensure adequate staffing in acute settings can improve staff satisfaction.…”
Section: Discussionsupporting
confidence: 72%
“…A recent qualitative study of health professionals identified the following beliefs that represent ‘best practice’ within centres providing renal replacement therapy (RRT). These were multi-disciplinary meetings, regular audit, assessment of staff performance, methods of staff communication and staff training to educate patients, but there was less consensus about staffing ratios and frequency of patient review [21]. There are limited data linking structural characteristics within organisations providing RRT and variation in quality of care.…”
Section: Can We Measure Underlying Factors Behind Centre Effects?mentioning
confidence: 99%
“…This scale was originally developed by investigators at UCLA and the RAND Corporation to evaluate appropriateness of different types of medical care (13,14). It has been used and validated as a measure of provider perceptions of various medical practices (12,15,16). The RAND scale may be trichotomized with the following interpretation: 1 to 3 ϭ "generally low impact;" 4 to 6 ϭ "moderate impact;" and 7 to 9 ϭ "generally high impact."…”
Section: Survey Overviewmentioning
confidence: 99%
“…IBPiD is a multidisciplinary research effort conducted through the University of California-Los Angeles (UCLA) in collaboration with the Renal Physicians Association (RPA) and the American Nephrology Nurses Association (ANNA) that aims to identify best practices that may improve facility-level achievement of clinical performance measures and overall outcomes in dialysis patients (12). As a part of IBPiD, we conducted a national survey in which we elicited caregiver perceptions regarding the extent and consequences of cherry picking in dialysis care.…”
mentioning
confidence: 99%